The Use of Internet-Based Digital PAI Learning Resources, Websites and Social Media at Al Azhar Excellent High School Medan - Nazliyani Pane; Icha Alfira Mahfi; Asyraful Khairi; Muhammad Ghozali Ma’arif (Journal of Multidisciplinary Science, 2024)
This study aims to explore the use of digital-based Islamic Religious Education (PAI) learning resources involving the internet, websites, and social media at SMA Unggulan Al-Azhar Medan. This study also aims to evaluate the effectiveness of digital learning resources and analyze the advantages and disadvantages that may arise in the use of digital PAI learning resources. The methodology applied in this research is a qualitative approach with a focus on SMA Unggulan Al-Azhar Medan as the research locus. The data collection process was conducted through observation, interview, literature study, and documentation techniques. The results showed that SMA Unggulan Al-Azhar Medan adopted digital learning resources, including the internet, websites, and social media in teaching PAI. The use of these digital PAI learning resources contributes positively, where around 80% of learners feel significant assistance in the learning process. The accessibility of digital resources makes it easier for teachers and learners to develop their thinking creativity in accordance with the demands of the times. However, this study also identified some challenges and weaknesses that need to be considered in the implementation of digital PAI learning resources in this educational context.